CHANGING BEHAVIOR OF JESSE AARONS IN GABOR CSUPO'S BRIDGE TO TERABITHIA MOVIE (2007): A BEHAVIORIST APPROACH - WARDANI, DIYAH (2011)
This study is aimed to show changing behavior of Jesse Aarons by using a behaviorism approach. It is done by establishing two objectives: the first is to analyze the film based on structural elements and the second is to analyze changing behavior of Jesse Aarons based on a behaviorist approach. The type of this research is qualitative research. In this method, the writer uses two data sources; they are primary and secondary data sources. The primary data source is from the script of the film Bridge to Terabithia. The secondary data source are taken from some books and websites. The result of the study shows that changing behavior of Jesse Aarons in Gabor Csupo's Bridge to Terabithia is reflected through characters and characterization, plot and theme. Gabor Csupo shows the role of every member in the environment especially friendship and peer comunity in shaping the major character behavior.